Pengembangan Permukiman Nelayan Kingking dan Karangsari Tuban Melalui Pendekatan Urban Assemblage - Santri, Tyas (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2020)
Indonesia is an archipelago country with a sea larger than the mainland, so it is undeniable that in Indonesia there are many fisherman settlements. Often fishermen settlements in Indonesia are marginalized in the development of maritime and service industries and even become victims of the activities of the utilization of coastal areas by the private sector engaged in tourism, industry, and services. The fisherman settlement community is not getting a positive impact from the development, therefore this study aims so that the fisherman settlement community can get a positive impact from the development of the surrounding area. This research takes a case study in the fisherman settlements of Kingking and Karangsari in Tuban Regency, East Java. The approach used in this research is the urban assemblage approach to reveal socio-cultural knits as a cultural force that shapes the sustainability of the place. The urban assemblage approach will be supported by search methods which will then be analyzed descriptively qualitatively. The search was carried out through literature review and field surveys. This research presents the results in the form of a mapping of knits between culture, social, the economy as the cultural strength of the Kingking and Karangsari fisherman settlements with the surrounding tourist areas. The results of this study can be considered by the government and local communities in planning the development of coastal areas or fisherman settlements into tourist destinations.